Low storage explicit Runge-Kutta method - Diomar Cesar Lobão (Semina: Ciências Exatas e Tecnológicas, 2019)
This paper we are dealing with the high order accurate low storage explicit Runge Kutta (LSERK) methods which mainly are used for temporal discretization and are stable regardless of its accuracy. The main objective of this paper is to compare traditional RK with different forms of LSERK methods. The numerical experiments indicate that such methods are highly accurate and effective for numerical purposes. It’s also shown the CPU time consuming and its solution implications. The method is well suited to achieve high order accurate solution for the scalar second order IVP (Initial Value Problem) problem as it is discussed in the present paper.